THE IMPACT OF PBWORKS APPLICATION ON VOCATIONAL STUDENTS’ COLLABORATIVE WRITING SKILL - Yundayani, Audi; Kardijan, Dian; Apriliani, Rainy Dwi (Jurnal Cakrawala Pendidikan, 2020)
Writing skill is a productive language skills that should be mastered by vocational students. It has become a critical issue in the study of English for Specific Purposes (ESP) and a challenging one in Indonesian context in the context of English as Foreign Language learning. This paper aims to investigate the impact of PBworks media application on vocational students’ collaborative writing skill. The research used the experimental approach. The respondents included 60 vocational students selected randomly and divided into two groups with 30 students in the control group and 30 students in the experimental group. The PBworks media was applied in the experimental group, while the control group received face-to-face writing class without incorporating learning media. The data were obtained by comparing student scores in the pre-test and two post-tests. The analysis of covariance (ANCOVA) was used to obtain the result. It showed that there is a statistically significant difference between using PBworks and non-Pbworks media in regard to the students’ writing performance (p < .05). Moreover, vocational students believe in the benefit of the PBworks media application in developing collaborative writing skill despite the disadvantages.